Validity of a Patient Communication Scale - Quinn, Joann Farrell; Khalid, Nikita; Albright, Glenn (Frontiers in Communication, 2023)
Background: Since the 1960s, standardized patients (SPs) have been used to prepare medical students for clinical work for these patients provide a controlled domain for learners. Specifically, these type of formative experiences provide a low stakes environment for practice and feedback, thereby increasing learner comfort in communicating with patients. Communication is the cornerstone of patient care, and it is well-established as a core clinical competency for medical students by numerous medical boards, associations, and accreditation agencies. While methods for communication training are of paramount importance, no validated scales assess the impact of these trainings on patient-provider communication where measures are based on attitudinal constructs that predict behavior, such as self-efficacy and preparedness. Thus, the aim of this study is to validate the Provider Patient Communication Scale (PPCS) using an online virtual role-play training simulation.To validate the scale, 117 medical students were administered the PPCS survey before and after completing a professional development virtual role-play simulation where they practiced motivational interviewing skills, talking to a patient who insists on antibiotics for a viral infection.A confirmatory factor analysis supported the two-factor model based on the subscales of preparedness and self-efficacy. Factor loadings showed all items correlated highly with theoretical constructs (r ≥ .902, p < .001). The PPCS had high internal consistency (α = .916). Because there is a lack of scales that have been used to assess medical student as well as medical practitioner patient communication capabilities, specifically their preparedness and self-efficacy, criterion-related validity was not assessed. Convergent, content and construct validity were established.The PPCS appears to be a valid tool in measuring the impact of online patientprovider communication skills training and holds promise for assessing other delivery methods.